Theorie der Architektur : Zeitgenössische Positionen. - Feldhusen, Sebastian (Bauwelt Fundamente., 2017)
"Theory of Architecture" as a research field engages manifold disciplines such as anthropology, architectural and art history, architectural and art theory, linguistics, philology, philosophy, psychology, sociology, and urbanism in a conversation on architecture. 24 authors present contemporary positions on the theory of architecture, which are arranged in three chapters that refer to the subjects of investigation: " concepts, discourses, ideas " things, spaces, buildings " practices, experiences, appropriations The book is published in honor of architectural theorist Eduard Führ. Authors: Böhringer, de Bruyn, Dreyer, Feldhusen, Friesen, Führ, Gleiter, Günter, Hahn, Harries, Hasse, Janson, Lampugnani, Leatherbarrow, Miller, Moravánszky, Neumeyer, Oechslin, Pérez-Gómez, Poerschke, Sieverts, Staub, Wagner